The assessment of efficiency of the use of the material and technical base of agriculture in the Russian Federation - A. V. Bondarchuk; N. V. Zhuravleva (Вестник Северо-Кавказского федерального университета, 2025)
Introduction. The challenging military-political situation in the Russian Federation, which leads to imbalance in all spheres of social development, has become an impetus for strengthening food security and the formation of food sovereignty. The development of the material and technical base of agriculture plays an important role in increasing agricultural productivity and is a factor of food security.Goal. The study aims to assess the level of development and efficiency of using the material and technical base of agriculture in the Russian Federation and its individual regions.Materials and methods. To achieve the goal, the article used general scientific research methods: methods of deduction and induction, methods of the economic and statistical method, the graphical method. The method of logic and generalization was used in the development of conclusions based on the results of the study.Results and discussion. The article examines the dynamics of production and import of agricultural machinery in Russia. It is proved that the reason for the high dependence on imported machinery is the narrow range of agricultural machinery produced. The share of the segment of agricultural machinery imports in the Russian Federation is considered, the provision of agricultural machinery to agricultural enterprises is analyzed. Attention is paid to the study of the level of renewal and liquidation of tractors in federal districts, as well as the provision of agricultural enterprises of the Russian Federation with tractors and combines. It is proved that the renewal of agricultural machinery directly affects the energy supply of agricultural organizations. Conclusion. According to the results of the study, it can be concluded that the under-equipment of agricultural enterprises with material and technical means threatens to disrupt food security not only in the regions, but also in the country as a whole.